Comprehensive assessment of exposure to clozapine in association with side effects among patients with treatment-resistant schizophrenia: a population pharmacokinetic study. (May 2021) - Nomura, Nobuyuki; Kitagawa, Kohei; So, Ryuhei; Misawa, Fuminari; Kodama, Masafumi; Takeuchi, Hiroyoshi; Bies, Robert; Straubinger, Thomas; Banker, Christopher; Mizuno, Yuya; Mimura, Masaru; Uchida, Hiroyuki
Background: There have been scarce data on the distribution of clozapine concentrations in comparison with the recommended range (350–600 ng/ml) or their relationship with side effects among patients with treatment-resistant schizophrenia. Furthermore, no studies have assessed the association between side effects and overall exposure to the drug by calculating the 24-h area-under-curve (AUC). Methods: In- and outpatients with schizophrenia or schizoaffective disorder (ICD-10) who were receiving a stable dose of clozapine for ⩾2 weeks were included. Side effects were assessed using the Glasgow antipsychotic side-effects scale for clozapine (GASS-C). Using two collected plasma samples, plasma clozapine and norclozapine concentrations at peak and trough and their 24-h AUC were estimated using population pharmacokinetic models. Results: A total of 108 patients completed the study (mean ± SD age, 43.0 ± 10.1 years; clozapine dose, 357.5 ± 136.9 mg/day); 33 patients (30.6%) showed estimated trough concentrations of clozapine within the recommended range (350–600 ng/ml) whereas the concentrations were higher and lower than this range among 37 (43.5%) and 28 (25.9%) patients (%), respectively. There were no significant correlations between estimated peak or trough concentrations or 24-h AUC of both clozapine or norclozapine, and GASS-C total or individual scores. No significant differences were found between GASS-C total or individual item scores between the patients with estimated trough concentrations of clozapine of >600 ng/ml and the other subjects. Conclusion: The results suggest that clozapine or norclozapine concentrations are not linked directly to the extent of side effects experienced in clozapine-treated patients with treatment-resistant schizophrenia while the cross-sectional study design limits the interpretation of any causal relationships. These findings indicate that side effects associated with clozapine may occur at any dose or concentration.